"دور المراقب المالي في الإدارة المسبقة على الصفقات العمومية - دراسة حالة مصالح الرقابة المالية لولاية الوادي" - زياد, زغيدي; حسيبة, غانم; صوالح عمار, مريم (جامعة الوادي - University of Eloued, 2023)
"إن الرقابة التي يمارسها المراقب المالي في مجال الصفقات العمومية لها أهمية كبيرة في حماية هذه الأخيرة من جميع التلاعبات، لهذا أعطى المشرع الجزائري أهمية قصوى للصفقات العمومية لأنها وسيلة من الوسائل التي تجسد فكرة استمرار المؤسسات العمومية وهي تخضع لطرق إبرام خاصة. ولقد جاء المرسوم الرئاسي رقم 15-247 المتضمن تنظيم الصفقات العمومية وتفويضات المرفق العام بصيغة مخالفة للنصوص السابقة لاسيما منها مرحلة الإبرام، وبالتالي حماية المال العام وهذا من خلال التأكد من عدم وجود تجاوزات ومخالفات للأنظمة والقوانين التي تحكم الصفقات العمومية . ولهذا فالمراقب المالي له دور أساسي لا يمكن الاستغناء عنه في عملية الرقابة على تنفيذ هذه الصفقات من خلال الرقابة السابقة عليها. " "The control exercised by the financial controller in public procurement is of great importance in protecting the latter from all manipulations. That is why the Algerian legislator gave most importance to public procurement because it is one of the means that ensure the idea of the continuity of public institutions and they are subject to special methods of conclusion. Presidential Decree No 15 245, which includes the regulation of public transactions and public utility authorizations in a manner contrary to the previous texts, especially the stage of conclusion, and thus protecting public money, and this is by ensuring that there are no abuses and violations of the regulations and laws governing public transactions. This financial controller has an essential role that cannot be dispensed with in the process of controlling the implementation of these deals through the previous control over them. "
Keywords: مراقب مالي صفقات عمومية ، طلب العروض إبرام شفافية، مصلحة مساواة، مال عام; Key words: Financial Controller, Public deals,Request for proposals, Conclusion, Transparency, An interest, Equality,Public money